KARAKTERISTIK SURAT TILANG DALAM PENINDAKAN PELANGGARAN LALU LINTAS DAN ANGKUTAN JALAN - Jemmy Jefry Pietersz (SASI, 2010)
Violations action in the field of Traffic and Transportation is the act of sanctioning violations. This action is done by issuing Surat Tilang as a result of the violations found in the inspection of motor vehicles on the road. Surat Tilang has characterized as a unilateral administrative action as a form of administrative sanctions against violations committed and does not require the court rulings against government actions that are unilateral. Thus, the Surat Tilang is categorized as an Administrative Decision.